(untitled) (Polifonia, 1995)
ABSTRACT: Through an analysis of the interaction between the "Governador Pmentel Menezes Public Library" and the slum of "Poço da Draga" in Fortaleza (Brazil), this study attmepts to show the polarity between public libraries and their potential underprivileged uders. Both poles have their own different codes which makes the dialog between them difficult. Nevertheless, as it is suggested by this study, the Smeiotics of Culture may now show wyas in which the two oples could get closer.